Cathodal transcranial direct current stimulation over posterior parietal cortex enhances distinct aspects of visual working memory. (1st July 2016) - Heinen, Klaartje; Sagliano, Laura; Candini, Michela; Husain, Masud; Cappelletti, Marinella; Zokaei, Nahid
Abstract: In this study, we investigated the effects of tDCS over the posterior parietal cortex (PPC) during a visual working memory (WM) task, which probes different sources of response error underlying the precision of WM recall. In two separate experiments, we demonstrated that tDCS enhanced WM precision when applied bilaterally over the PPC, independent of electrode configuration. In a third experiment, we demonstrated with unilateral electrode configuration over the right PPC, that only cathodal tDCS enhanced WM precision and only when baseline performance was low. Looking at the effects on underlying sources of error, we found that cathodal stimulation enhanced the probability of correct target response across all participants by reducing feature-misbinding. Only for low-baseline performers, cathodal stimulation also reduced variability of recall. We conclude that cathodal- but not anodal tDCS can improve WM precision by preventing feature-misbinding and hereby enhancing attentional selection. For low-baseline performers, cathodal tDCS also protects the memory trace. Furthermore, stimulation over bilateral PPC is more potent than unilateral cathodal tDCS in enhancing general WM precision. Highlights: Despite multiple studies, reported effects of tDCS on cognitive processes have remained variable. We employ a WM task that probes different underlying sources of error to test effect of tDCS separately. tDCS applied bilaterally to the PPC boosts WM precision. Unilateral stimulation indicates this is caused by cathodal- rather than anodal stimulation. Improvement relies particularly on enhanced selective attention as well as memory trace protection.